Dinamika dan Pengerucutan Teori Gerakan Sosial - Hasanuddin (Nakhoda: Jurnal Ilmu Pemerintahan, 2011)
This article aims to describe of dynamic and reduction social movement theory. Emergent of socialmovement theory get our see from two aspect. First, from relationship between framing with politicalchanges thinking. Twice, correlation reciprocal between framing with mobilization. Success orunsuccessfull from movement depend of organization movement capability to present third organizationalfactor. That are disruptive tactics, radical flank effects and goals.Keywords: social movement theory, dynamic, reduction